Objectives and Standards : An Approach to Planning and Control - Bélanger, Paul (Relations industrielles / Industrial Relations, 1967)
This article reviews "Objectives and Standards : An Approach to Planning and Control" by Ernest C. Miller.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z